Consumer decision-making in bottled water purchases: The case of Aqua in Palangka Raya - Harjoni, Harjoni; Sopather, Kembara (JSM: Jurnal Sains Manajemen, 2025)
The rapid urbanization and growing awareness of health and safety have fueled the global consumption of bottled water, with Indonesia emerging as a major market in Southeast Asia. Brands like Aqua dominate due to their consistent product quality and strong distribution networks. This study explores the factors influencing consumer decision-making in purchasing Aqua bottled water in Palangka Raya, Central Kalimantan. The research aims to assess how demographic characteristics—such as occupation, income, and education—relate to consumer perceptions of price, quality, health benefits, packaging, taste, and brand prestige. The study employed a quantitative descriptive method using the Chi-Square test (χ²) to analyze categorical variables based on survey responses from 200 Aqua consumers across two subdistricts. The findings reveal that while income level does not significantly influence consumer perception across the examined dimensions, significant relationships were observed between occupation and perceived product quality, as well as between education level and brand prestige. Consumers with formal employment and higher education tend to view Aqua more positively in these aspects. Overall, Aqua is perceived favorably for its refreshing taste, appealing packaging, and brand prestige, despite being considered relatively expensive. These findings suggest that brand trust and product reliability are prioritized over price sensitivity. The study recommends that Aqua’s marketing strategies further target professional and educated consumer segments through messaging that reinforces quality and social status. Limitations of the study include its cross-sectional nature and narrow geographical scope. Future research should incorporate qualitative methods and broader variables such as environmental awareness and brand loyalty to gain deeper insights into consumer preferences in the bottled water industry.